Assessment Of Bidirectional Relationship Between Diabetes And Chronic Periodontitis By Evaluating Blood Glucose Levels Using Sulcular And Venous Blood In Chronic Periodontitis After Non-Surgical Periodontal Therapy - A Cross Sectional Study (Journal of Pharmaceutical Negative Results, 2023)
Background: Diabetes and chronic periodontitis (CP) act as bidirectional manner. Dental office DM screening could result in earlier treatment and possible minimization of serious complications.Objective: objective of the present study was to compare the efficacy of blood glucose level using conventional venous blood (VB) and gingival sulcular blood (GSB) samples in CP patients having type II diabetes before and after non-surgical periodontal therapy (NSPT).Material and methods: A total of 250 CP stage I/II patients with type II DM were divided into control (VB) and test (GSB) group. VB and GSB were evaluated for blood glucose level after NSPT at 3 months and compared with baseline.Results: Mean blood glucose level at baseline for test group was 204.71 ± 82.51 and control group was 203.86 ± 87.78 mg/dl (p=0.41) which was statistically non-significant. Both the VB and GSB was effective to evaluate diabetic status. Blood glucose level before and 3 month after NSPT showed statistically significant difference (p=0.026) for test group and highly statistical significance (p=0.001) for control group. Karl Pearson’s product–moment correlation (r) for groups: The Pearson correlation coefficient R was counted to measure the strength and direction of the relationship between two variables. The R value between control and test group was 0.98 at baseline and 0.99 at 3 months. It shows a strongly positive co-relation.Conclusion: Diabetes and chronic periodontitis has a bi-directional relation. Periodontal therapy helps to maintain better blood glucose level. Successful periodontal maintenance is also dependent on diabetic status of the patient.